The impact of food commodity imports on the Sudanese trade balance: (2018–2000م) - د. احمد ضو البيت احمد; د. مروة عبد القادر صالح (White Nile Journal for Studies and Research, 2021)
Abstract This Study aimed to Measuring the Impact of Imports of food Commodities on The Sudanese trade balance and Measuring the Impact of total Imports on the trade balance in Sudan the problem of the study is that the Sudanese trade balance has been suffering from an almost permanent deficit throughout the study period, in order to outweigh the Sudanese imports over export. The study aimed to measure and demonstrate the impact of imports of food commodities on the Sudanese trade balance, because it has remained a semi-permanent deficit. Following the Econometric approach namely the the ordinary least squares method (OLS) through E views program to estimate the relationship between trade balance and food imports. Using data about the study variables for the period from 2000-2018 and the use of the most important hypotheses of the study are the existence of a positive relationship between imports of food commodities and the Sudanese trade balance, due to the existence of the deficit that has been associated with the Sudanese trade balance. The most important results of the study are the presence of a strong positive significant impact on the volume of food commodity imports on the Sudanese trade balance during the study period, due to the fact that food commodities represent the actual needs of society. The most important recommendations of the study must be concerned with the production of food commodities, which the state avoids importing from other countries and contributes to improving the trade balance in Sudan Keywords: the Sudanese economy the trade balance- food imports